Upaya Kanwil Kementerian Agama Sumatera Barat Membumikan Moderasi Beragama - Khoiriah, Ulfa; Wahyuni, Sri; Oktari, Dea Wana; Jamalius, Rido; Shalihin, Nurus; Yusuf, M (Universitas Islam Negeri Imam Bonjol Padang, 2023)
This article aims to examine the strategies of the Regional Office of the Ministry of Religious Affairs (Kanwil Kemenag) in transforming the idea of religious moderation among the people of West Sumatra. The study is a qualitative research using interview and literature review techniques. The interview was conducted with one civil servant and an employee at the Kanwil Kemenag office in West Sumatra, while the literature review referred to the official news website of Kanwil Kemenag in West Sumatra. The findings of this article indicate that Kanwil Kemenag's efforts include first, conducting training and socialization on religious moderation for several elements of society. Second, forming a task force for religious moderation. The targets of the activities carried out by Kanwil Kemenag in promoting the growth of religious moderation include the community, civil servant educators, non-civil servant educators, heads of Islamic religious affairs offices, school principals, religious leaders, students of Islamic high schools and middle schools, as well as the entire components of Islamic higher education institutions. As a subsystem in society, Kanwil Kemenag in West Sumatra has successfully carried out four structural-functional functions in creating a harmonious diversity in West Sumatra society.Artikel ini bertujuan untuk melihat strategi Kanwil Kemenag dalam mentransformasikan gagasan moderasi beragama pada masyarakat Sumatera Barat. Studi ini merupakan penelitian kualitatif dengan teknik wawancara dan studi pustaka. Wawancara dilakukan terhadap salah satu ASN dan pegawai di kantor Kanwil Kemenag Sumbar, dan studi pustaka merujuk terhadap website berita resmi Kanwil Kemenag Sumbar. Temuan artikel ini menunjukkan bahwa upaya-upaya yang dilakukan Kanwil Kemenag Sumbar diantaranya pertama, melaksanakan pelatihan dan sosialiasi moderasi beragama bagi beberapa elemen masyarakat. Kedua, membentuk satgas moderasi beragama. Adapun yang menjadi sasaran dalam kegiatan-kegiatan yang dilakukan Kanwil Kemenag Sumbar dengan upaya menumbuh kembangkan moderasi beragama adalah masyarakat, penyuluh PNS, penyuluh non PNS, Kepala KUA, Kepala Sekolah, Penghulu, Siswa MAN dan MTSN, serta PTKIN, beserta seluruh komponennya. Sebagai sub sistem dalam masyarakat Kanwil Kemenag Sumbar telah berhasil menjalankan empat fungsi (struktural fungsional) dalam menciptakan keberagaman yang harmonis di masyarakat Sumatera Barat.